Mechanisms of aggregation inhibition by aspirin and nitrate-aspirin prodrugs in human platelets. - GILMER, JOHN (My University, 2012)
Objectives Aspirin is the mainstay of anti-platelet therapy in the secondary prevention of cardiovascular disease. However, problems with aspirin safety and resistance demand clinical strategies based on multiple pharmacological approaches. Prodrugs of aspirin may offer beneficial effects in terms of gastro-intestinal safety and multiple pharmacological approaches. However, the pharmacological profile of aspirin prodrugs in human platelets has not been completed yet. We aimed to compare the effects of aspirin and prodrugs of aspirin (1-5) on human platelet aggregation stimulated by ADP and collagen and associated receptor expression (GPIIb/IIIa and P-selectin) in platelet-rich plasma (PRP) and washed platelets (WP). Methods As aspirin is released from prodrugs following esterase hydrolysis we studied the expression and activity of butyrylcholineterase (BuChE) and carboxyesterase (CE) in plasma and platelets. The mechanism of prodrug-induced platelet aggregation inhibition was explored by studying the effects of plasma and purified human BuChE on aggregation. Finally, the relative contribution of nitric oxide (NO) bioactivity to nitrate-containing prodrugs of aspirin-induced inhibition of aggregation was determined using 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ,) a selective inhibitor of the soluble guanylyl cyclase. Key findings ST0702, 2, a nicotinic acid-aspirin codrug was equipotent with aspirin with respect to inhibition of collagen-induced platelet aggregation. Compound 4, a NO releasing aspirin was the most potent inhibitor of ADP-induced platelet aggregation, an effect partially reversed by ODQ. The platelet inhibitory effects of aspirin prodrugs were time-dependent as the maximal inhibitory effects against collagen-induced aggregation were achieved by aspirin at 2 min, 1 at 5 min and ST0702 at 15 min. The aspirin prodrugs were significantly less potent in WP than in PRP and the reverse was true of aspirin. In the presence of complete BuChE inhibition in PRP, there was almost complete loss of aspirin prodrug, but not aspirin anti-aggregatory activity. Interestingly, CE activity was observed in WP and platelet lysate with pNPA substrate. Accordingly, 1 and ST0702 retained 50% and 100% anti-aggregatory activity at maximal concentrations in WP, which was attenuated in the presence of esterase inhibitor phenylmethylsulphonyl fluoride. Conclusions The inhibitory effect of aspirin prodrugs in PRP is due to prodrug activation by BuChE. In contrast, the platelet-inhibitory effects of aspirin prodrugs in WP may be mediated through the activity of platelet CE. Compound 4, a NO-containing aspirin prodrug, may exert dual inhibitory effects in platelets. Thus, aspirin prodrugs effectively inhibit human platelet aggregation and as such may be an alternative to conventional aspirin.
PUBLISHED
Keywords: Aspirin; Aspirin